Chromium Oxide‐modified Mesoporous Zirconium Dioxide: Efficient Heterogeneous Catalyst for the Synthesis of 5‐Hydroxymethylfurfural. Issue 19 (30th August 2022) - Wang, Xiaojun; Lu, Ni; Fu, Yuanyi; Lu, Chang; Guan, Meili; Wang, Kunhua; Yu, Hao
Abstract: A highly efficient carbohydrate conversion to 5‐hydroxymethylfurfural (5‐HMF) is a promising method to achieve green and sustainable development. However, most currently reported strategies are energy consuming, and the 5‐HMF yield is relatively lower in the aqueous phase. Herein, a facile method is reported to obtain effective Cr/ZrO2 catalysts with high acidity and their catalytic performances were investigated for catalyzing fructose to 5‐HMF at different temperatures and times. With the catalysis of 15 % Cr/ZrO2 catalyst, the highest fructose conversion of 98 %, 5‐HMF yield of 48.8 %, and 5‐HMF selectivity of 49.8 % are achieved in green solvent with good recyclability. The possible reaction process of the improved catalysis performance is attributed to the highly crystalline and strong acidity of the Cr/ZrO2 catalyst. The Lewis acid sites could increase the overall rate of fructose conversion by promoting side reactions and might suppress fructose to glucose isomerization. In addition, Cr leakage during the reaction might act as the Bronsted acids to catalyze the fructose dehydration to 5‐HMF. The reported method of introducing chromium oxides into ZrO2 catalyst will open a new avenue to promote the practical application of biomass and sustainable development in the future. Abstract : A chromium oxide‐modified mesoporous zirconium dioxide catalyst has been prepared for the efficient conversion of biomass to 5‐hydroxymethylfurfural.